LANGUAGE AS A BRANDING TOOL: LINGUISTIC TACTICS IN INDIE PUBLISHERS’ SOCIAL MEDIA CAMPAIGNS - Rawuh Yuda Yuwana; Acep Fatchuroji (PT Akselerasi Karya Mandiri, 2026)
This study examines the linguistic and semiotic strategies employed by indie publishers on social media to construct branding identities within the digital literacy ecosystem. Using qualitative discourse analysis, digital linguistics, and multimodal semiotics, the study analyzes 15 social media posts across Instagram, TikTok, Twitter (X), Facebook, and official websites. The findings identify five recurring linguistic strategies: emotional micro-narratives, conversational positioning, multimodal linguistic framing, community-aligned hashtagging, and metaphorical semiotic branding. Collectively, these strategies position indie publishers as humanistic, approachable, and literacy-oriented actors despite limited marketing resources. This study contributes theoretical insight into how small cultural agents construct visibility, identity, and relational engagement through language in competitive digital spaces.